Requirements for the Design and Implementation of Post-Earthquake Permanent Housing (Case Study of Sari District Three) - Abdolmajid Khorshidian; Akbar Zargar (مسکن و محیط روستا, 2018)
Recent earthquake experiences in Iran have shown that housing reconstruction is one of the most important aspects of post-earthquake recovery programs. Therefore, the provision of high quality housing that can meet the needs and expectations of people is a key factor in the success of reconstruction programs. However, recent experiences have shown that achieving this goal faces many challenges. Delay in delivery, escalating costs, poor quality and residents' dissatisfaction are the most common problems. Municipal district 3 located in the south of Sari is exposed to a high seismic risk and due to its worn-out urban environment, it is highly vulnerable. Problems such as the economic constraints of low-income residents, local construction weaknesses, low interaction between the community and built-environment professionals, lack of awareness of residents and insufficient capacity of local builders have led to a high risk in the district. These conditions necessitate a pre-earthquake planning for the reconstruction of permanent housing. Due to a lack of guidelines on earthquake risk reduction and shelter and housing provision after an earthquake in the city of Sari, the present paper examines the key dimensions of the design and implementation of post-earthquake permanent housing in this district. The results of this study can inform decision making for permanent housing, earthquake risk reduction and accelerating and improving the efficiency of permanent housing reconstruction after disasters. The article uses a case study approach to achieve this goal. First, it examines existing theories and identifies the most important dimensions and challenges of providing permanent housing and then considers them in the studied area. The results of the field study are validated through expert opinion elicitation. Qualitative interviews and observation have been used as data collection techniques. Semi-structured interviews have been conducted with three groups of participants: local residents, post-disaster reconstruction specialists and authorities. Samples were selected through purposive and snowball sampling based on the knowledge and experience of the participants. Data analysis relies on thematic analysis. In this method, the analysis is based on themes or dimensions that have been extracted from the literature review in relation to the research problem. These dimensions were the basis for selecting the interview questions during the data collection and for coding the responses in the data analysis phase. Finally, the findings of the field study were validated by the views of the reconstruction experts and were used to identify the key guidelines for housing reconstruction in the study area. In general four main themes have been deduced. These themes consist of; 1) implementation requirements; 2) design approach; 3) economic responses; and 4) socio-culture considerations. These themes have a significant impact on the efficiency of the housing reconstruction project and the satisfaction of residents. In this regard, the theme of implementation requirements includes issues such as settlement location; housing repair and retrofitting; stages of post-earthquake sheltering and housing; and considering reconstruction as a development opportunity for vulnerability reduction. The theme of economic responses provides housing affordability solutions for low-income residents in the district, and then examines the role of housing in household livelihoods. Finally, the categories of compatibility with settlement pattern; the restoration of local identity; and responding to the residents' expectations, are emphasized in the theme of socio-cultural considerations.